Global Trends and Research Evolution of XBRL Adoption in Financial Reporting - Judijanto, Loso; Wifasari, Septi; Rianto, Rianto; Eldianson, Rio; Riny, Riny (Eastasouth Institute, 2025)
This study explores the global trends and intellectual structure of research on XBRL (eXtensible Business Reporting Language) adoption in financial reporting through a comprehensive bibliometric analysis. Utilizing the Scopus database and VOSviewer software, data from 2000 to 2024 were analyzed to identify publication patterns, author collaborations, thematic clusters, and emerging research frontiers. The results indicate that early research predominantly focused on the technical and administrative aspects of XBRL implementation, particularly in the context of financial reporting standardization. Over time, the field has shifted toward evaluating the regulatory, economic, and organizational impacts of XBRL, including its role in reducing information asymmetry, enhancing investor transparency, and aligning with global reporting frameworks such as IFRS. The United States emerged as the leading contributor, while growing scholarly interest is observed in emerging economies like Malaysia and Jordan. Keyword co-occurrence analysis highlights evolving themes and the interdisciplinary nature of the field, suggesting opportunities for deeper theoretical engagement and broader geographic inclusion. This study offers a strategic overview of the development of XBRL research and identifies key directions for future inquiry.